Characteristics of a long and stable filamentary argon plasma jet generated in ambient atmosphere. (7th April 2015) - Teodorescu, M; Bazavan, M; Ionita, E R; Dinescu, G
Abstract: We present a study of a long (up to 60 mm) and thin (600  μ m) plasma jet generated at 13.56 MHz in argon expanding in an open atmosphere from inside of a thin glass tube. The discharge is operated with one annular external electrode on the tube, in the absence of any grounded electrode in the discharge proximity. The study comprises image, spectral and electrical measurements, aiming to define and understand the operating domains of this plasma jet source. Two plasma zones were identified, which coexist: a long filament accompanied by a diffuse discharge. The coexistence of these plasma zones was studied in the power-mass flow rate parameter space. An electric model is proposed, considering the jet as a radiating antenna, which allows the determination of the main electrical parameters like capacitance, resistance and active RF power dissipated in the discharge. The specific zones on the I – V characteristics were assigned to the operating domains observed visually. The spectral emission of plasma has been used to characterize the jet in respect to the gas temperature, excitation temperature and plasma density.